2017
DOI: 10.2334/josnusd.16-0235
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo</i> evaluation of chitosan-glycerol gel scaffolds seeded with stem cells for full-thickness mandibular bone regeneration

Abstract: The aim of this study was to evaluate in vivo bone regeneration, mediated by adipose-derived stem cells (ADSCs), induced to differentiate into osteoblasts and carried by a scaffold gel. In the test group, bone regeneration was mediated by ADSCs, induced to differentiate into osteoblasts, and carried by a scaffold gel. In the control group a scaffold without cells was used. The scaffold, consisting of chitosan and glycerol phosphate, was maintained in situ by a cross-linked resorbable membrane. The osteogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…For chondrogenic or osteogenic regeneration, the spontaneous adipogenic differentiation of ADSCs should be minimized as possible. Adipogenic, chondrogenic, and osteogenic differentiation was observed in passage 3 in many studies (29)(30)(31)(32)(33)(34). The results of the present study indicated that the impact of spontaneous adipogenic differentiation reduced sufficiently after passage 3, and the cells passaged more than three times were probably suitable for chondrogenic and osteogenic regeneration.…”
Section: Discussionsupporting
confidence: 59%
“…For chondrogenic or osteogenic regeneration, the spontaneous adipogenic differentiation of ADSCs should be minimized as possible. Adipogenic, chondrogenic, and osteogenic differentiation was observed in passage 3 in many studies (29)(30)(31)(32)(33)(34). The results of the present study indicated that the impact of spontaneous adipogenic differentiation reduced sufficiently after passage 3, and the cells passaged more than three times were probably suitable for chondrogenic and osteogenic regeneration.…”
Section: Discussionsupporting
confidence: 59%
“…Maglione et al. demonstrated the osteogenic potential of ASCs further by seeding them onto a chitosan-glycerol phosphate hybrid gel scaffold, which was maintained by in-situ by cross-linking [382] . The scaffolds were implanted into full-thickness mandible defects, with ex vivo histological and micro CT analysis performed after 8 weeks.…”
Section: Materials Used Within Bone Tissue Engineeringmentioning
confidence: 99%
“…Hydrogels based on carboxymethyl chitosan (CMC) and oxidized chondroitin sulfate (OCS) were prepared and loaded with bovine serum albumin (BSA) for in vitro degradation and BSA release of the CMs/gel scaffolds evaluation [26]. In vivo evaluation of chitosan-glycerol incorporating stem cells were evaluated for mandibular bone regeneration, exhibiting an exciting osteogenic potential [27]. Relevant literature for hydrogel and nanogels for biomedical applications has been published recently [28].…”
Section: Introductionmentioning
confidence: 99%